Is there an optimal pole length for double poling in cross country skiing? - Onasch, F.; Killick, A.; Herzog, W. (Journal of Applied Biomechanics, 2017)
The aim of this study was to determine the effects of pole length on energy cost and kinematics in cross country double poling. Seven sub-elite male athletes were tested using pole sets of different lengths (ranging between 77% and 98% of participants` body height). Tests were conducted on a treadmill, set to a 2% incline and an approximate racing speed. Poling forces, contact times, and oxygen uptake were measured throughout the testing. Pole length was positively correlated with ground contact time (r=.57, p<001) and negatively correlated with poling frequency (r=-.48, p=.003). Pole length was also positively correlated with pole recovery time and propulsive impulse produced per poling cycle (r=.36, p=.031; r=.35, p=.042, respectively). Oxygen uptake and pole length were negatively correlated (r=-.51, p=.004). This acute study shows that increasing pole length for double poling in sub-elite cross country skiers under the given conditions seems to change the poling mechanics in distinct ways, resulting in a more efficient poling action by decreasing an athlete`s metabolic cost. ABSTRACT FROM AUTHOR